The Effect of Impervious Layer Depth on the Uplift Water pressure beneath the Gate Location in the Hydraulic Structures - Faisal A. Al Tabatabaie; Dhabia Sabeeh Al Waily (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Because of the maximum uplift water pressure usually became under the gate of the hydraulic structures, so in this research a determination of the uplift pressureunder the gate location was investigated by using a finite element method with the Geo- studio 2016 software together with experimental work by using electrical analogue model to compare the results obtained from the two methods and to show the accuracy of the electrical analogue model to simplify solving the seepage problems under the hydraulic structures. The experiments were carried out in the electrical laboratory, Kut Technical Institute, for four cases of impervious layer at different depths of (75, 60, 45, 30) cm respectively, and each case consisted of (25) models, the flow net was plotted for each case and the total was (100) cases to determine the uplift pressure beneath the gate location. The experimental flownets and results were compared with the results of Geo-studio software program, both results shown a good agreement between them approach to (92.561)%.